Identification of Aspergillus species in diwal (Pholas orientalis) from Pontevedra, Negros Occidental. - Lumio, Chiarela Gracia T.
Oriental Angelwings or Diwal (Pholas orientalis), is endemic in Western Visayas particularly in some parts of Negros Occidental. However, data about the fungal organisms associated with Diwal are limited and hardly any data had been published. Thus, this study provides an identification of Aspergillus species found in Diwal collected from Pontevedra, Negros Occidental using morphological characteristics. The gut, gills, mantle, siphon, and shell swab of Diwal were examined for the presence of Aspergillus species and come up with identification to the genus and species level. Environmental samples such as sediment, seawater, and larval water were also examined to describe the ecology of Diwal. Results revealed 69 isolates of Aspergillus found in the different parts of diwal belonging to eight (8) species; A. flavus fumigatus, A. glaucus, A. nidulans, A. niger, A. oryzae, A. terreus, and A. ustus. Measured in terms of frequency of occurrence, A. flavus is the most occuring (30.43 percent) while A. terreus (1.45 percent) is the least occurring. Most of which were found in the gut (29 percent) and occurred least in the mantle, siphon, and swab with similar frequencies of occurrence (18.84 percent). Additionally, twelve Aspergillus isolates belonging to five (5) species; A. flavus, A. nidulans, A. oryzae, A. terreus, and A. ustus were identified in the nevironmental samples. 75 percent of which were found in the sediment, and were infrequent in the alrval water (8.33 percent). This identification potentially provides basis for monitoring the health of the shellfish population as well as their ecological condition and symbiotic relationship with fungi and other organisms associated with Diwal. Being able to label microorganisms, such as the Aspergillus species of fungi, which affect the florishing of Diwal, will help larger-scale researches of environmental and economic importance to develop strategies to resolve the existing problems, of species extinction for instance, and to prevent further problems.